Factors Associated with Suicidal Ideation and Quality of Life in Adolescents from Puerto Rico with Type 1 Diabetes - Guerrero-Ramírez, Grace; Cumba-Avilés, Eduardo (Puerto Rico Health Sciences Journal, 2018)
Objective: People with type 1 diabetes (T1D) may experience significant changes in their daily routines due to this condition, which frequently results in depressive symptoms and the deterioration of their quality of life. We examined the factors associated with suicidal ideation (SI) and diabetes-related quality of life (DRQOL) in adolescents (aged 12 to 17) with T1D. Methods: The sample consisted of 51 youths (29 girls) recruited during a treatment study for depression. They completed the Diabetes Quality of Life for Youth questionnaire, the Suicidal Ideation Questionnaire Junior, and other measures that explore emotional, cognitive, somatic, behavioral, and relational aspects. Their caregivers completed the Barriers to Adherence Questionnaire and the Somatic Complaints subscale of the Child Behavior Checklist, among other measures. We used correlation and multiple linear regression analyses to identify the factors associated with the dependent variables. Results: The variables associated with SI were depression, somatic complaints, perceived family emotional support, self care for diabetes, self-deprecation, helplessness, and hopelessness, among others. In a multiple regression analysis, the first 3 accounted for 46% of the variance. Those related to DRQOL included cognitive alterations, barriers to adherence, perceived family emotional support, self-efficacy for diabetes and for depression, helplessness, anxiety, and self-deprecation, among others. The first 4 accounted for 61% of the variance. Conclusion: Our findings highlight the impact of emotional, cognitive, somatic, behavioral, and relational aspects on the quality of mental health and the DRQOL of youth with T1D, as well as their pertinence for the development of psychosocial interventions for this population.